On Aboriginal Religion. - Stanner, W. E. H. (Sydney University Press, 2022)
Anthropologist W.E.H. Stanner is perhaps most well known for coining the phrase the 'great Australian silence', addressing the culture of denial or 'conscious forgetting' regarding the history Australia since European arrival.